Relationship between Blood Lipids, Lipoproteins and Ischemic Stroke (Bangladesh Journal of Neuroscience, 2014)
Objective: To find out the relationship of different lipids, lipoproteins and ischemic stroke patients in Bangladesh.Methodology: This case control study was conducted among the patients having ischemic stroke who were admitted in Department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period from July, 1997 to June, 1999 and age, sex matched apparently healthy volunteers. Sixty ischemic stroke patients confirmed by CT scan of brain and sixty age and sex matched apparently healthy volunteers were enrolled as controls. 12 hours fasting lipid profile (Total cholesterol, LDL-cholesterol, HDLcholesterol and Triglyceride) was done for both ischemic stroke patients and healthy volunteers for comparison. The students (unpaired) t test was used to compare group means for lipids and lipoproteins. Chi square test, odds ratio with confidence interval were done to evaluate differences between the groups for other variables. P